Effect of Shorter Pretreatment Time on Clinical and Neonatal Outcomes in Human Blastocysts Vitrification after Artificial Shrinkage - Liuguang Zhang; Romualdo Sciorio; Yuhu Li; Ning Li (IMR Press, 2023)
Background: Prolonged pretreatment time may be harmful to frozen embryo's developmental potential. This study was conducted to evaluate the effect of different equilibration times on the clinical and neonatal outcomes of frozen-warmed blastocyst transfer. Methods: This is a retrospective study based on data collected from our medical records from March 2018 to March 2022 and including a total of 763 expanded blastocysts from 538 warming blastocyst cycles. These cycles were divided into two groups according to the equilibration time: (A) 6-7 minutes, and (B) 9-10 minutes. The survival rate, clinical, and neonatal outcomes were investigated. Results: The survival, implantation, and clinical pregnancy rates of vitrified-warmed shrinkage blastocyst were not different between the two groups. Other variables analyzed including live birth, multiple gestation, and neonatal outcomes were similar between the two groups. Conclusions: The results of this study illustrated that vitrification of artificially collapsed blastocysts with a shorter equilibration time (6-7 minutes) and pre-vitrification is able to lead to similar clinical and neonatal outcomes in patients undergoing assisted reproductive technology (ART).